THE IMPLEMENTATION OF ACCELERATED LEARNING MODEL MASTER TYPE TO IMPROVE THE MOTIVATION AND ICT LEARNING ACHIEVEMENT OF VIII B CLASS STUDENTS OF SMP NEGERI 1 SAWAN IN SEMESTER II IN THE ACADEMIC YEAR OF 2011/2012 - Nyoman Satiawan (Universitas Pendidikan Ganesha, 2012)
This research was aimed at: 1) improving students’ learning motivation at class VIII B of SMP Negeri 1 Sawan in the academic year of 2011/2012 in ICT subjects through the implementation of Accelerated Learning model MASTER type, 2) improving students’ learning achievement at class VIII B of SMP Negeri 1 Sawan in the academic year of 2011/2012 in ICT subjects through the implementation of Accelerated Learning model MASTER type, and 3) to find out students’ response toward the implementation of Accelerated Learning model MASTER type. This study was a Classroom Action Research (CAR), in which the subjects of this research were class VIII students of SMP Negeri 1 Sawan in second semester in the academic year of 2011/2012.The objects of study were students’ learning motivation, students’ learning achievement, and students’ responses toward the implementation of Accelerated Learning model MASTER type. Data of learning motivation were collected by using questionnaire of ICT learning motivation; data about the students’ learning achievement were obtained through cognitive tests, and observation sheets for affective and psychomotor. Meanwhile, the data of students’ response were collected by using closed questionnaire at the end of the second cycle or at the end of the study. Furthermore the data obtained were analyzed descriptively. The results showed that: 1) there was an improvement on the students' learning motivation, it could be seen from the mean score of learning motivation on cycle I, that was 53.75 with a high category, while in the cycle II improved to 56.47, it was also considered as high category as well, 2) the mean score of students’ learning achievement improved 7,44, from 73.95 in cycle I to 81.39 in cycle II. Classical completeness increased by 36,11%, students who are in category finished in the cycle I is 63,89% and increased in the cycle II to 100% 3) the students’ response to the implementation of Accelerated Learning model MASTER type on ICT subjects were positive with mean score of 63.17.